Modern HERstory : stories of women and nonbinary people rewriting history - Imani, Blair (Ten Speed Press, 2018)
"An illustrated and informative primer on the progressive social change movements of the last 60 years as told through the stories of 60 diverse female and non-binary leaders in those movements, from the Civil Rights Movement and Stonewall riots through today. Inspiring a radical and inclusive approach to history, Modern HERstory celebrates 60 modern women and non-binary people who have changed the world. From the civil rights movement and the women's movement to the LGBT rights movement and Black Lives Matter, these trailblazers come from backgrounds and communities that are traditionally overlooked and under-celebrated despite making huge contributions to the social change and progress movements of the last century: not just women, but people of color, queer people, trans people, Muslims, and young people. Authored by rising star activist Blair Imani, Modern HERstory tells the important stories of these leaders and their movements in an easy-to-follow format appropriate for all ages, granting them the visibility and acknowledgment they deserve, and educating readers about the people changing the world right here and right now--and inspiring them to do the same"--